2011
DOI: 10.1016/j.jhealeco.2011.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Changes in compulsory schooling and the causal effect of education on health: Evidence from Germany

Abstract: In this paper, we investigate the causal effect of years of schooling on health and healthrelated behavior in West Germany. We apply an instrumental variables approach using changes in compulsory schooling laws which took place from 1949 to 1969 as natural experiments. These law changed generate exogenous variation in years of schooling both across states and over time. We find evidence for a strong and significant causal effect of years of schooling on long-term illness for men but not for women. Moreover, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
194
4
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(226 citation statements)
references
References 30 publications
22
194
4
6
Order By: Relevance
“…The coefficients are very small, negative and insignificant. Thus, consistent with previous findings, we do not find evidence that the reform affected track choice (see, e.g., Pischke & von Wachter 2008, Kemptner et al 2011, Piopiunik 2011. 20…”
Section: Effect Of Education On the Number Of Children And Childlessnesssupporting
confidence: 91%
“…The coefficients are very small, negative and insignificant. Thus, consistent with previous findings, we do not find evidence that the reform affected track choice (see, e.g., Pischke & von Wachter 2008, Kemptner et al 2011, Piopiunik 2011. 20…”
Section: Effect Of Education On the Number Of Children And Childlessnesssupporting
confidence: 91%
“…In line with the second prediction, various studies report positive education effects on health behaviors [4,10,40,50,61]. For instance, using data on a major schooling information campaign in the Dominican Republic, [36] find that schooling significantly reduces smoking and delays the onset of daily or regular drinking among male students.…”
Section: Theoretical Framework and Empirical Literaturementioning
confidence: 77%
“…In line with this argument, previous studies have found education to positively influence health-related lifestyles and behaviors, such as smoking [36,38,40,64], drinking [36], or care seeking [53,56]. Despite this evidence, little is known about the actual mechanisms through which education affects behavioral patterns.…”
Section: Introductionmentioning
confidence: 98%
“…One counter-example to this is a study of changes in German compulsory schooling laws applied between 1949 and 1969; it finds that additional schooling decreased the risk of long-term illness and disability for men aged between 40 and 70 [7].…”
Section: Studies Exploiting Compulsory Schooling Changesmentioning
confidence: 99%